Impacts of Climate Change on Human Health and Adaptation Strategies for Nepal - Dhimal, M; Bhusal, CL (Journal of Nepal Health Research Council, 2010)
DOI: 10.3126/jnhrc.v7i2.3025 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 140-141